The novel Los dorados by Sergio Muñoz: Hierarchy and exclusion in Costa Rican society - Rojas Rodríguez, María Eugenia (2026)
Sergio Muñoz text explains the socioeconomicproblems of the Costa Rican community, which are tangible and evident. The contribution of his story revealsthe character life in order to exceed the reality by meansof the dialogue with the reader.The novel takes place in marginal urban life andshores the daily life of some excluded human beings. Itis a story from the below, and the depicts inside andoutside of the abusers, the alcoholics, the prostitutes,single mothers, the deprived of liberty, which in somecases have already served their sentences, itinerantmerchants, those who invade someone else’s invade land, and presents children, men and women trying tosurvive in this so unequal world.